Can Einstein’s Theory of General Relativity be Taught to Indonesian High School Students? - Dua, Y. S.; Blair, D. G.; Kaur, T.; Choudhary, R. K. (Jurnal Pendidikan IPA Indonesia, 2020)
The detections of gravitational waves, which culminated in the 2017 physics Noble Prize award have again confirmed the triumph of the theory of general relativity. This theory, together with quantum mechanics, forms the backbones of our modern understanding of the world and significantly contributes to modern technologies we are using today. Despite the importance of these theories, they are still rarely part of high school physics curricula worldwide, including the Indonesian physics curriculum, due to assumptions that these theories are too difficult for students to grasp. However, there has been a growing interest to bring these theories to younger students and general public and there is growing evidence that appropriate teaching can result in measurable learning. The purpose of this research was to explore the impact of activity-based learning using models and analogies on high school studentsÃ¢â‚¬â„¢ conceptual understanding of general relativity related concepts. It was conducted in one class of 31 students who participated in a three-week period program. Testing of their conceptual understanding used identical pre/post-tests. The results indicated a strong and statistically significant improvement in studentsÃ¢â‚¬â„¢ conceptual understanding with a large effect size. Interestingly, the results showed that the change in conceptual understanding to physics of girls was higher than boys.Ã‚Â Ã‚Â